Exploring pastoralist social cohesion across two consecutive drought periods: Insights from Borena, Fuldowa Kebele - Flintan, Fiona E.; Assefa, Amanuel; Ebro, Abule (International Livestock Research Institute, 2024)
A presentation of initial research findings on pastoralist social cohesion across two consecutive drought periods in pastoral areas of Ethiopia, with a focus on the sharing of food aid. Presented at the roundtable on Risk Transformation and Societal Resilience Under Extreme Events, IDOS Bonn, 28-29 November 2024, organized by the German Research Foundation.